Probiotic and Prebiotic-probiotic PEC Microparticles for Sustaining and Enhancing Intestinal Probiotic Growth - Harshitha, K.; Kulkarni, P.K.; Vaghela, Rudra; Naga Sravan Kumar Varma, V.; Rohan Deshpande, D.; Hani, Umme (Current Drug Delivery, 2015)
The aim of the study was to develop and evaluate Polyelectrolyte complex (PEC) microparticles composing Lactobacillus Acidophilus (probiotic) and Fructo oligosaccharide-Lactobacillus Acidophilus (prebiotic-probiotic), for sustaining and enhancing intestinal growth of probiotic bacteria. Gum Karaya-Chitosan(GK-CH) was used to fabricate PEC microparticles by extrusion method. The prepared microparticles were characterized for FT-IR, DSC and particle size and evaluated for percentage yield, swelling, surface morphology, entrapment rate and further studied for influence of prebiotic over probiotic growth. The fabricated PEC microparticles composed of Probiotic and Prebiotic- Probiotic have exhibited sustainability of probiotic bacteria for 12 hrs in GIT conditions and presence of prebiotic in the preparation enhanced the probiotic cell growth. Hence, it can be concluded that PEC between GK-CH was found to be successful in sustaining cell release and presence of prebiotic was found to enhance the probiotic cell growth.
Keywords: probiotic